Community holds key to curb spread of IS militants - New Sarawak, Tribune (New Sarawak Tribune, 2015)
MELAKA: It is not the power of the police, army or might of sophisticated weapons which serve as the bastion to curb the spread of the socalled IS militant dogma in the country.